An investigation on factors influencing the intention to use e-money: A case study in Pontianak, Indonesia - Yuni Nustini; Fariz Zhafiri (Jurnal Akuntansi dan Auditing Indonesia, 2020)
This study is to examine the factors influencing Pontianak citizens to use e-money in response to the state regulation. The investigated factors include perceived usefulness, perceived ease of use, perceived risk, and quality of service. Attitude toward the use of e-money was determined as the intervening variable to the intention to use e-money. Pontianak as a developing city in Borneo Island has been piloted to fully utilize electronic money to purchase fuel in gas stations. Meanwhile, so far Indonesians living in developing regions are not yet familiar with the advanced payment technology such as e-money. The samples were taken randomly from the gas station consumers in Pontianak. The number of samples collected was 100 and the data were processed using SmartPLS 3.0. The results of the study showed that all of the hypotheses were supported except perceived risk variable. In addition, the effect size of the intervening variable “attitude” in the relationships between perceived usefulness and the intention to use e-money as well as perceived ease of use and the intention to use e-money were categorized as full mediation. Meanwhile, the effect size of attitude in the relationship between quality of service and the intention to use e-money was categorized as quasi mediation. However, attitude did not have mediating effect on the perceived risk. The effect size of the mediating variable was proved large at the value of 1.981. Since the people of Pontianak represent those who were much familiar with cash transactions, the results of this study can be considered as an example for the implementation of e-money payment in other developing regions or for the execution of certain technology-based non-cash programs.